Microwave Induced Stereoselective Conversion of Dialkyl 2-(Imido-yl)-3- (Triphenylphosphoranylidene)butanedioates to Electron-poor (Z)-Vinylimides in the Presence of Silica Gel Powder in Solvent-free Conditions - Ramazani, Ali; Abbasi Motejadded, Akram; Ahmadi, Ebrahim (Asian Journal of Chemistry, 2010)
Silica gel was found to catalyze stereoselective conversion of dialkyl 2-(imido-N-yl)-3-(triphenylphosphoranylidene)butanedioates to electron-poor (Z)-N-vinylimides in solventfree conditions under microwave irradiation.